Peran Orang Tua dalam Mendorong Partisipasi Anak Usia Dini pada Aktivitas Olahraga - Anindya Wanda Prameswari; Rivan Saghita Pratama (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
This literature review discusses permissive parenting and its impact on the development of golden age children with a focus on broken home families. The purpose of this study is to provide a deeper understanding of how permissive parenting affects the social-emotional development of golden age children and provide constructive solutions to overcome the negative impacts of this parenting pattern. The research method is carried out through a literature review by collecting and analyzing relevant sources of information. Permissive parenting is reviewed from the concept, characteristics, influence of factors, and its positive and negative impacts on the development phase of golden age children. This study identifies the weaknesses of previous studies and offers a more comprehensive solution by focusing on permissive parenting. The results of the analysis show that permissive parenting can provide benefits in the expression of creativity and autonomy of children, but can also cause difficulties in dealing with boundaries and self-regulation. The importance of parenting is emphasized, because it has a significant impact on the development and well-being of children. The relationship between parenting and the surrounding environment is also considered, illustrating how social norms and the school environment can influence the implementation of parenting patterns. Thus, this study provides in-depth insight into the issue of permissive parenting in golden age children, offers a broader understanding of parenting issues, and provides a basis for practical development guidelines for parents in supporting optimal child development.